Methodological quality of case series studies: an introduction to the JBI critical appraisal tool. Issue 10 (23rd October 2020) - Munn, Zachary; Barker, Timothy Hugh; Moola, Sandeep; Tufanaru, Catalin; Stern, Cindy; McArthur, Alexa; Stephenson, Matthew; Aromataris, Edoardo
ABSTRACT: Introduction: Systematic reviews provide a rigorous synthesis of the best available evidence regarding a certain question. Where high-quality evidence is lacking, systematic reviewers may choose to rely on case series studies to provide information in relation to their question. However, to date there has been limited guidance on how to incorporate case series studies within systematic reviews assessing the effectiveness of an intervention, particularly with reference to assessing the methodological quality or risk of bias of these studies. Methods: An international working group was formed to review the methodological literature regarding case series as a form of evidence for inclusion in systematic reviews. The group then developed a critical appraisal tool based on the epidemiological literature relating to bias within these studies. This was then piloted, reviewed, and approved by JBI's international Scientific Committee. Results: The JBI critical appraisal tool for case series studies includes 10 questions addressing the internal validity and risk of bias of case series designs, particularly confounding, selection, and information bias, in addition to the importance of clear reporting. Conclusion: In certain situations, case series designs may represent the best available evidence to inform clinical practice. The JBI critical appraisal tool for case series offers systematic reviewers an approved method to assess the methodological quality of these studies.